Neuropsychological Subgroups of Emotion Processing in Youths With Conduct Disorder - Kohls, Gregor; Fairchild, Graeme; Bernhard, Anka; Martinelli, Anne; Smaragdi, Areti; Gonzalez-Madruga, Karen; Wells, Amy; Rogers, Jack C.; Pauli, Ruth; Oldenhof, Helena; Jansen, Lucres; Rhijn, Arthur van; et al. (Frontiers in Psychiatry, 2020)
Background: At the group level, youths with conduct disorder (CD) show deficient emotion processing across various tasks compared to typically developing controls (TDC). But little is known about neuropsychological subgroups within the CD population, the clinical correlates of emotion processing deficits [for instance, with regard to the presence or absence of the DSM-5 Limited Prosocial Emotions (LPE) specifier], and associated risk factors. Methods: 542 children and adolescents with CD (317 girls) and 710 TDCs (479 girls), aged 9–18 years, were included from the FemNAT-CD multisite study. All participants completed three neuropsychological tasks assessing emotion recognition, emotion learning, and emotion regulation. We used a self-report measure of callous-unemotional traits to create a proxy for the LPE specifier. Results: Relative to TDCs, youths with CD as a group performed worse in all three emotion domains. But using clinically based cut-off scores, we found poor emotion recognition skills in only 23% of the participants with CD, followed by emotion regulation deficits in 18%, and emotion learning deficits in 13% of the CD group. Critically, the majority of youths with CD (~56%) did not demonstrate any meaningful neuropsychological deficit, and only a very small proportion showed pervasive deficits across all three domains (~1%). Further analyses indicate that established DSM-5 subtypes of CD are not tightly linked to neurocognitive deficits in one particular emotion domain over another (i.e., emotion recognition deficits in CD+LPE vs. emotion regulation deficits in CD–LPE). Conclusions: Findings from this large-scale data set suggest substantial neuropsychological diversity in emotion processing in the CD population and, consequently, only a subgroup of youths with CD are likely to benefit from additional behavioral interventions specifically targeting emotion processing mechanisms.